LACTIC ACID BACTERIA FROM CINCALUK AND THE ACTIVITY AGAINST Vibrio alginolyticus AND Aeromonas hydrophila - Nursyirwani, Nursyirwani; BP, Valentina Dian; Effendi, Irwan (Asian Journal of Aquatic Sciences, 2018)
Lactic acid bacteria (LAB) has been applied as probiotic mainly to prevent pathogens. This group of bacteria can be found in marine fish products including fermented, shrimp product, cincaluk. The objective of this research was to isolate LAB from cincaluk, and examined the activity against pathogen V. alginolyticus and A. hydrophila. The research was conducted on March Juny, total of 12 isolates were obtained from cincaluk survey method. The result of research showed that all isolates round, creamy white, smooth edged, raised surface, and the size is 1.0 to 3.0 mm. The physiological and biochemical test showed that get all isolates had a Gram positive, catalase positive and are indole negative, 10 isolates were motile, as many as five isolates have citric positive, 10 isolates is Methyl Red (+), all isolates ferment sucrose and lactose, while only 9 isolates ferment glucose, and as much as 6 isolates that produce sulfide. All isolates were found to have inhibitory effects against bacteria V. alginolyticus and A. hydrophila. The highest antimicrobial activity is indicated by B isolates with an average diameter of 12.3 mm and inhibition zone antivibrio activity of 6.3 units. Isolates B with an average diameter of inhibition zone of 9.7 mm and 3.7 units antiaeromonas activity.